Pengaruh Kepemilikan Manajerial Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan Dengan Kepemilikan Institusional Sebagai Variabel Moderasi - Yamashita; Agam Mei Yudha; Rindy Citra Dewi; Deni Saputra (Journal Of Science Education And Management Business, 2022)
This study aims to determine how much influence Managerial Ownership and Company Growth have on Firm Value with Institutional Ownership as a Moderating Variable (In Manufacturing Companies listed on the Indonesia Stock Exchange for the 2016-2020 period). From this research, the following conclusions are obtained: (1) There is a significant influence between Managerial Ownership on Company Value. (2) There is a significant influence between the growth of the company on the value of the company. (3) There is a significant influence between Managerial Ownership and Company Growth on Firm Value. (4) Managerial ownership partially has a significant effect on firm value with institutional ownership as a moderating variable. (5) Company growth partially has no significant effect on firm value with institutional ownership as a moderating variable in the company (6) managerial ownership and company growth partially significant effect on firm value with institutional ownership as a moderating variable